Studi Resepsi Khalayak terhadap Pemberitaan Syariat Islam pada Kompas.com - Uswatun Nisa (Jurnal Komunikasi Global, 2017)
Sharia news in the mass media often implies that the sharia implemented in Aceh is not tolerant of some groups. This study aims to explore the reception by Aceh audiences towards sharia news in the national online media, Kompas.com from 2014 to 2016, as well as to know the factors behind the audience in making meaning. Aspects of the sharia coverage that become the object study in this research are the image of sharia, the efforts of local governments in implementing sharia law, the role of Islamic scholars in the enforcement of sharia, the image of sharia police, and the position of women in the implementation of sharia. The main concept used is encoding/decoding by Stuart Hall. This research used constructivism paradigm with reception analysis method. The interpretation of the same news made by the seven participants on five aspects is widely varied according to the framework of knowledge and experience of each informant. The most dominant reading position occupied by informants is oppositional reading, followed by negotiated reading, and very few informants in dominant reading position. The differences of reading positions are influenced by sociological, psychological, and media habit factors of each informant.